(х+7)(х-2)-(х+4)(х+3)= -2 Помогите решить уравнение!

(х+7)(х-2)-(х+4)(х+3)= -2 Помогите решить уравнение!
Гость
Ответ(ы) на вопрос:
Гость
[latex](x+7)(x-2)-(x+4)(x+3)=-2[/latex] [latex](x+7)(x-2)-(x-4)(x+3)+2=0[/latex] [latex](x^2-2x+7x-14)-(x^2+3x+4x+12)+2=0[/latex] [latex](x^2+5x-14)-(x^2+7x+12)+2=0[/latex] [latex]x^2+5x-14-x^2-7x-12+2=0[/latex] [latex]-2x-24=0[/latex] [latex]-2x=24[/latex] [latex]x=24:(-2)[/latex] [latex]x=-12[/latex] [latex]Otvet:-12.[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы